Accelerated Aortic Flow Assessment with Compressed Sensing With and Without Use of the Sparsity of the Complex Difference Image - Kwak, Yongjun (2012)
Phase contrast (PC) cardiac MR (CMR) is widely used for the clinical assessment of blood flow in cardiovascular disease. One of the challenges of PC CMR is the long scan time which limits both spatial and temporal resolution. Compressed sensing (CS) reconstruction with accelerated PC acquisitions is a promising technique to increase the scan efficiency. In this study, we sought to utilize the sparsity of the complex difference (CD) of the two flow-encoded images as an additional constraint term to improve the CS reconstruction of the corresponding accelerated PC data acquisition. Using retrospectively under-sampled data, the proposed reconstruction technique was optimized and validated in-vivo on 15 healthy subjects. Then, prospectively under-sampled data was acquired on 11 healthy subjects and reconstructed with the proposed technique. The results show that there is good agreement between the cardiac output measurements from the fully-sampled data and the proposed CS reconstruction method using CD sparsity up to acceleration rate 5. In conclusion, we have developed and evaluated an improved reconstruction technique for accelerated PC CMR that utilizes the sparsity of the CD of the two flow-encoded images.